VD_FINDINFO Décision / 2012 / 917 vom 13. August 2012 - VD Tribunal cantonal (2012)
CLASSEMENT DE LA PROCÉDURE, COMPÉTENCE RATIONE LOCI, MENACEDROIT PÉNAL | 180 CP, 29 CPP (CH), 310 CPP (CH), 393 al. 1 let. a CPP (CH)